Optimization and Validation Test of Self Nano-emulsifiying Drug Delivery System Capsule of Ethanol Extract Parang Romang Leaves - Magfirah Magfirah; Indah Kurnia Utami; I Dewa Ayu Nurllya K.D; Niluh Puspita Dewi (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introdiction: Parang romang contains alkaloids, flavonoids, tannins, and saponins. The secondary metabolites of the leaf extract have low solubility in water. The self-nano emulsifying drug delivery system (SNEDDS) is one solution to increase the solubility of the extract. Aims This study aims to obtain the best formula and ensure that the assay analysis method used can provide accurate and reliable results so that they can be trusted. Methods: Parang romang leaf extract was added to the optimum mixture of tween 20/80, propylene glycol, and olive oil and then characterized including% transmittance, drug loading, emulsification time, particle size, index polydispersity, zeta potential, dissolution test, Scanning electron microscopy (SEM ) and validation of the analysis method including linearity, precision, accuracy, LOD, and LOQ. Result: The results showed the ratio of surfactant, co-surfactant, and olive oil which produced the optimum formula for SNEDDS, namely 26 ml; 17.5 ml; and 6.5 ml,% transmittance 85.90, drug loading 45.36, emulsification time for AGF, AIF, and aqua dest was 15-16 seconds, particle size 404.1 nm, index polydispersity 0.840, zeta potential -31.4 mV, dissolution test 92.13%, SEM in the form of spherical chunks, and the result of the validation test of the analytical method with a linearity of r = 0.9902, precision 0.436%, accuracy 103.738%, LOD 1.87 Âµ / ml and LOQ 5.57 Âµ / ml. SNEDDS parang romang leaf extract using olive oil as the oil phase, Tween 80 as a surfactant, and propylene glycol as a cosurfactant provide optimal nanoemulsion characteristics and validation of the analytical method meets the requirements. Conclusion: Formula 1 SNEDDS parang romang leaf extract using olive oil as the oil phase, Tween 80 as a surfactant, and propylene glycol as a cosurfactant is an optimal formula that provides good nanoemulsion characteristics and validation of analytical methods meets the requirements